Moral Violations and the Experience of Disgust and Anger - Oaten, Megan; Stevenson, Richard J.; Williams, Mark A.; Rich, Anina N.; Butko, Marina; Case, Trevor I. (Frontiers in Behavioral Neuroscience, 2018)
Disgust is a natural defensive emotion that has evolved to protect against potential sources of contamination and has been recently linked to moral judgements in many studies. However, that people often report feelings of disgust when thinking about feces or moral transgressions alike does not necessarily mean that the same mechanisms mediate these reactions. The present study used functional magnetic resonance imaging (n= 22) to investigate whether core and moral disgusts entrain common neural systems. We provide evidence that: (i) activation of overlapping brain regions between core and moral disgust is the result of content overlap in the vignettes – core disgust elicitors – across conditions, and not from moral violations per se, and (ii) moral residue (i.e., the remaining or “residual” activation after the influence of core disgust elicitors have been taken into account) produced a pattern of activation that is more consistent with moral anger, than one of ‘residual disgust’. These findings run contrary to the premise that our “moral centre” is connected to the area of the brain in which physical revulsion is located.